Childhood cancer burden: a review of global estimates. Issue 1 (January 2019) - Bhakta, Nickhill; Force, Lisa M; Allemani, Claudia; Atun, Rifat; Bray, Freddie; Coleman, Michel P; Steliarova-Foucher, Eva; Frazier, A Lindsay; Robison, Leslie L; Rodriguez-Galindo, Carlos; Fitzmaurice, Christina
Summary: 5-year net survival of children and adolescents diagnosed with cancer is approximately 80% in many high-income countries. This estimate is encouraging as it shows the substantial progress that has been made in the diagnosis and treatment of childhood cancer. Unfortunately, scarce data are available for low-income and middle-income countries (LMICs), where nearly 90% of children with cancer reside, suggesting that global survival estimates are substantially worse in these regions. As LMICs are undergoing a rapid epidemiological transition, with a shifting burden from infectious diseases to non-communicable diseases, cancer care for all ages has become a global focus. To improve outcomes for children and adolescents diagnosed with cancer worldwide, an accurate appraisal of the global burden of childhood cancer is a necessary first step. In this Review, we analyse four studies of the global cancer burden that included data for children and adolescents. Each study used various overlapping and non-overlapping statistical approaches and outcome metrics. Moreover, to provide guidance on improving future estimates of the childhood global cancer burden, we propose several recommendations to strengthen data collection and standardise analyses. Ultimately, these data could help stakeholders to develop plans for national and institutional cancer programmes, with the overall aim of helping to reduce the global burden of cancer in children and adolescents.